Economic Lyapunov‐based model predictive control with event‐triggered parametric identification. (5th October 2021) - Zheng, Yi; Li, Shaoyuan; Wan, Ruoxiao; Wang, Yanye
Abstract: This article focuses on the design of model predictive control (MPC) for nonlinear systems with slow time‐dynamic change. To avoid frequent updates of the predictive model and guarantee the state always stays inside of a given feasible region, an event‐triggered parametric estimation mechanism is designed. Firstly, a trigger condition is designed to judge if parameters of the predictive model are out of date and differ a lot from their current true values so that there is no feasible solution to regulate the state within the given bound without predictive model parameter update. This condition also depends on the current state and is deduced from a designed Lyapunov constraint, inputs constraints, and the mismatched predictive model. Then the EMPC is designed based on this condition. If the trigger condition is met, the MPC recursively updates the parameters and imposes the Lyapunov constraint. The Lyapunov constraint is based on the mismatched model and the real state does not need to be convergence. Else, the MPC only optimizes the cost function to derive a good profit. We proved that the proposed EMPC promises that the closed‐loop system state is maintained within a predefined stable region when the model mismatch bound can be estimated accurately. A simulation of a chemical process demonstrates the effectiveness of the proposed method.